Subclinical myocardial dysfunction of the left ventricular in patients with systemic lupus erythematosus - R. A. Karateev; I. G. Kirillova; Yu. N. Gorbunova; T. V. Popkova (Научно-практическая ревматология)
The aim – to study the frequency of left ventricular (LV) myocardial dysfunction and its relationship with disease activity in patients with systemic lupus erythematosus (SLE).Materials and methods. The study included 100 patients with SLE who met the criteria of SLICC/ACR 2012, 87% were women, the average age was 33 [25; 40] years, the average duration of the disease was 1 [1; 9] year, patients with varying degrees of activity according to SLEDAI-2K (low/moderate/high) – 30/45/25 (30%/45%/25%). All the subjects had not previously received biological therapy and had no previously diagnosed cardiovascular diseases and other rheumatic diseases. All patients received glucocorticoids (GCs) and hydroxychloroquine therapy in different dosages depending on the severity of the disease, according to the standards recommended by the Association of Rheumatologists of Russia from 2021. Methotrexate was received by 6% of patients, azathioprine – 14%, cyclophosphamide – 3%, nonsteroidal anti-inflammatory drugs – 81.2%. The control group consisted of 20 healthy individuals, having no signs of rheumatic diseases and CVD comparable in age and gender. All the subjects underwent echocardiography (ECHO) with tissue dopplerography and left ventricle global longitudinal strain (LV GLS) assessment by speckle tracking.Results. Violation of LV GLS was observed in 65 (65%) patients with SLE. In the SLE group, compared with the control group, a significantly more damaged LV GLS was revealed. In all patients with impaired diastolic function of the left ventricular myocardium, deterioration of LV GLS parameters is observed. Impairment of LV GLS correlated with clinical and immunological parameters in patients with SLE: the degree of SLE activity according to SLEDAI-2K (r=0.219), the level of antibodies to double-stranded DNA (a/b to ds-DNA) (r=0.316), the C3 level of the complement component (r=–0.389), the C4 level of the complement component (r=–0.238), the hemoglobin level (r=–0.255), the number of red blood cells (r=–0.286), the level of C-reactive protein (r=–0.284) and CRP (r=–0.927). Also, patients with SLE with diagnosed nephritis (n=26) had a significant violation of LV GLS parameters.Conclusions. In patients with SLE, according to ECHO using the Speckle tracking technique, violation of LV GLS occurs with a high frequency (65%). Violation of LV GLS parameters is associated with SLE activity, immunological and hematological disorders. In all patients with impaired diastolic function of the left ventricular myocardium, LV GLS was obviously decreased. The presence of lupus nephritis is associated with a significant violation of the GLS parameters.